Inadequate lung development and bronchial hyperplasia in mice with a targeted deletion in the Dutt1/Robo1 gene. - Xian, J; Clark, K; Fordham, R; Pannell, R; Rabbitts, T; Rabbitts, P (2001)
Chromosome 3 allele loss in preinvasive bronchial abnormalities and carcinogen-exposed, histologically normal bronchial epithelium indicates that it is an early, possibly the first, somatic genetic change in lung tumor development. Candidate tumor suppressor genes have been isolated from within distinct 3p regions implicated by heterozygous and homozygous allele loss. We have proposed that DUTT1, nested within homozygously deleted regions at 3p12-13, is the tumor suppressor gene that deletion-mapping and tumor suppression assays indicate is located in proximal 3p. The same gene, ROBO1 (accession number ), was independently isolated as the human homologue of the Drosophila gene, Roundabout. The gene, coding for a receptor with a domain structure of the neural-cell adhesion molecule family, is widely expressed and has been implicated in the guidance and migration of axons, myoblasts, and leukocytes in vertebrates. A deleted form of the gene, which mimics a naturally occurring, tumor-associated human homozygous deletion of exon 2 of DUTT1/ROBO1, was introduced into the mouse germ line. Mice homozygous for this targeted mutation, which eliminates the first Ig domain of Dutt1/Robo1, frequently die at birth of respiratory failure because of delayed lung maturation. Lungs from these mice have reduced air spaces and increased mesenchyme, features that are present some days before birth. Survivors acquire extensive bronchial epithelial abnormalities including hyperplasia, providing evidence of a functional relationship between a 3p gene and the development of bronchial abnormalities associated with early lung cancer.